Clinical outcomes of antithrombin III‐based therapy for patients with portal vein thrombosis: A retrospective, multicenter study. Issue 1 (4th October 2022) - Hayama, Korenobu; Atsukawa, Masanori; Tsubota, Akihito; Kondo, Chisa; Iwasa, Motoh; Hasegawa, Hiroshi; Takaguchi, Koichi; Tsutsui, Akemi; Uojima, Haruki; Hidaka, Hisashi; Okubo, Hironao; Suzuki, Tatsuya; et al.
Abstract: Aim: The association between thrombolytic therapy and the outcome in patients with portal vein thrombosis (PVT) remains controversial. This study aimed to evaluate the outcome in patients with PVT who received antithrombin III‐based therapy. Methods: This study was a retrospective, multicenter study to investigate the liver‐related events and the survival rates in 240 patients with PVT who received the therapy. Results: The patients comprised 151 men and 89 women, with a median age of 69 years. The rate of favorable response, defined as maximum area of PVT changed to ≤75%, was 67.5% (162/240). The cumulative rates of liver‐related events at 1, 2, and 3 years were 38.2%, 53.9%, and 68.5%, respectively. The multivariate analysis showed that viable hepatocellular carcinoma, absence of maintenance therapy, non‐responder, and PVT progression were significantly associated with liver‐related events. The PVT progression was observed in 23.3% (56/240). The multivariate analysis identified older age, absence of maintenance therapy, and non‐responder as independent factors associated with PVT progression. The multivariate analysis revealed that younger age, no hepatocellular carcinoma, presence of maintenance therapy, and lower Model for End‐stage Liver Disease‐Sodium score significantly contributed to 3‐year survival. Of the 240 patients, 13 (8.9%) prematurely discontinued treatment due to any adverse events. Conclusions: This study suggests that maintenance therapy, favorable response, and absence of PVT progression may suppress or control liver‐related events in antithrombin III‐based therapy for patients with PVT. Specifically, maintenance therapy could suppress not only liver‐related events, but also PVT progression and improve the prognosis.